CTA's UAV4Ag and drones in agribusiness experiences - Rambaldi, Giacomo (Technical Centre for Agricultural and Rural Cooperation, 2018)
Giacomo Rambaldi, Senior Programme Coordinator at CTA, shares the experience of CTA working on technology and innovation in agriculture, specially focusing on the use of drone technology since 2015.